„Freikauf“ oder „Erlösung in Jesus Christus“? (Röm 3,24): Exegetische Überlegungen zu einer nicht vernachlässigbaren Frage der Römerbrief-Exegese - Wypadlo, Adrian (Biblische Zeitschrift, 2022)
This contribution examines the lexeme ἡ ἀπολύτρωσις in the top text of Paul’s doctrine of justification in Rom 3:21–31 exegetically. In particular, one should ask how the syntagma διὰ τῆς ἀπολυτρώσεως τῆς ἐν Χριστῷ Ἰησοῦ in Rom 3:24b is to be translated correctly. The interpretation is based on the hermeneutical assumption of a translation of ἀπολύτρωσις with “free purchase” or “redemption”. It is important to consider whether the propositio generalis and especially the syntagma δύναμις … εἰς σωτηρίαν in Rom 1:16–17 can contribute aspects to the decision of this translation. Last but not least, it is asked which fields of imagination are called up by the urban Roman Christians through the use of the metaphor of ransom.